5-HT2 receptor activation in the midbrain periaqueductal grey (PAG) reduces anxiety-like behaviour in mice - Nunes-de-Souza, Vanessa; Nunes-de-Souza, Ricardo Luiz [UNESP]; Rodgers, Robert John; Canto-de-Souza, Azair (Elsevier B.V., 2008)
It is widely acknowledged that the indoleamine neurotransmitter serotonin (5-HT) plays a dual role in the regulation of anxiety, a role that in part depends upon neuroanatomical locus of action. Thus, whereas stimulation of 5-HT1A or 5-HT2 receptors in the limbic forebrain (amygdala, hippocampus) enhances anxiety-like responding in rodents, activation of corresponding receptor populations in the midbrain periaqueductal grey (PAG) more often than not reduce anxiety-like behaviour. The present study specifically concerns the anxiety-modulating influence of 5-HT2 receptors within the mouse PAG. Experiment 1 assessed the effects of intra-PAG infusions of the 5-HT2B/2C receptor agonist mCPP (0, 0.03, 0.1 or 0.3 nmol/0.1 mu l) on the behaviour of mice exposed to the elevated plus-maze. As mCPP acts preferentially at 5-HT2B and 5-HT2C receptors, Experiment 2 investigated its effects in animals pretreated with ketanserin, a preferential 5-HT2A/2C receptor antagonist. In both cases, test sessions were videotaped and subsequently, scored for anxiety-like behaviour (e.g., percentage of open arm entries and percentage of open arm time) as well as general locomotor activity (closed arm entries). The results of Experiment I showed that mCPP microinfusions (0.03 and 0.1 nmol) into the PAG of mice decreased behavioural indices of anxiety without significantly altering general activity measures. In Experiment 2, the anxiolytic-like profile of intra-PAG mCPP (0.03 nmol) was substantially attenuated by intra-PAG pretreatment with an intrinsically inactive dose of the preferential 5-HT2A/2C receptor antagonist, ketanserin (10 nmol/0.1 mu l). Together, these data suggest that 5HT(2C) receptor populations within the midbrain PAG play an inhibitory role in plus-maze anxiety in mice. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: anxiety; elevated plus-maze; 5-HT2 receptors; mCPP; ketanserin; PAG; mice